Alive the true story of a triumph of the human spirit - Watts, Robert; Marshall, Frank (Paramount pictures and touchstone pictures, 2002)
On the afternoon of friday, October 13, 1972, one of the most controversial and inspirational tales of survival began when an airplane carrying a team of young rugby players from Uruguay crashed into the Andes mountains. Several of the passengers died instantly but most survived. for eight days, they sat and waited to be rescued. But help never came and they learnt from the radio that the search had been abandoned. Soon their food and drink were gone. Forced to exist in sub-Zero weather for ten weeks, the survivors endured the unimaginable by doing the unthinkable until three of the boys, Nando Parrado (Ethan Hawke), Antonio Balbi (vincent Spano anbd Roberto Canessa (Josh Hamilton) left camp in an heroic attempt to trek out of the mountains for help.